Experimental and Numerical Study on the Capability Behavior of a Thick-Walled Spatial Cast-Steel Joint under Complex Load Conditions - Binghan Zhang; Bin Yang; Tiankai Wu; Dayu Zhu; Ke Lei (Advances in Civil Engineering)
A cast-steel joint is always used as an important component for the safety of the whole structure at key points, and the capability of the joint is important for the cast-steel joint. This paper conducts an experimental and numerical study on a 1/2 scale model of a joint in a real project. The experiment is used to validate the numerical model and then make further studies on the behavior of the joint by using a numerical method. Combining the result of the scale model test and numerical analysis shows that the joint can bear the prescribed load and it is still in the elastic stage. This paper also discusses the influence of the absence of the secondary moment, torque, and shear force. For the core area of the joint, the secondary moment and torque have little effect on the stress distribution, and the axial force of the secondary branches can increase the capability of the joint. But the secondary shear forces do have some effect on the stress of core area, and an enhancement coefficient is used to enlarge the axial force and moment to cover the absence of shear in the test.